Gambaran Waktu Clearing Xylol dan Minyak Kayu Putih Terhadap Kualitas Preparat Awetan Ctenocephalides Canis - Novi Yuniar; Faisal Faisal; Erni Yohani Mahtuti; Previta Zeizar Rahmawati (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Making durable preparations includes a fixation process using 10% KOH, dehydration, clearing and mounting. Clearing aims to make the morphological structure of a sample or object appear clearer, more transparent and clearer. In this research, the solution used was xylol solution and eucalyptus oil. Xylol is a solution that is not environmentally friendly, because it comes from petroleum or liquid asphalt. Meanwhile, eucalyptus oil is a solution obtained from the distillation of eucalyptus leaves which is environmentally friendly and easy to obtain and has non-polar properties which can remove residues in paraffin in preparations, so it can be used as a substitute for xylol. This research aims to describe the quality of preserved Ctenocephalides canis preparations in the clearing process using xylol and eucalyptus oil. The samples in this study were 24 adult Ctenocephalides canis. The results of the study showed that the durable preparations using xylol received 4 good preparations, 5 fairly good preparations, and 3 poor preparations. Meanwhile, the results of durable preparations using eucalyptus oil were 5 good preparations, 6 quite good preparations, and 1 bad preparation. So it can be concluded that making permanent preserved preparations for Ctenocephalides canis is better using eucalyptus oil compared to xylol.